Transforming Research Archives into Collective Memory : A Practice-Based Reflection on a National Virtual Exhibition through Indonesia’s Archival Network - Aulianto, Dwi Ridho (ARCHIVIST: Indonesian Journal of Archival, 2026)
Digital archives are increasingly understood not merely as passive repositories of scientific documentation, but as active spaces for public engagement and collective meaning-making. This paper presents a practice-based reflection on the transformation of research archives into collective memory through a national virtual exhibition hosted within Indonesia’s archival network. Drawing on the case of the LAPAN-Tubsat virtual exhibition, Indonesia’s first micro-satellite curated by the National Research and Innovation Agency (BRIN) through the National Archival Information Network (JIKN), the study examines how archival curation, digital storytelling, and participatory communication converge in practice. The reflection highlights the role of metadata integrity, interoperability, and interpretive design in maintaining archival authenticity while enhancing public accessibility. Through interdisciplinary collaboration and iterative curatorial processes, the initiative demonstrates how scientific records can be reimagined as communicative heritage that connects research evidence with national memory. The paper offers insights into professional transformation, ethical access, and digital governance, proposing a transferable practice model for research archives within the Global South.